“They Just Went After Us:” Reproductive Justice Advocacy at an Abortion Fund - Gantt-Shafer, Jessica (Frontiers in Communication, 2020)
In this study, I explore how organizers at an abortion fund use new media to create communication outreach about abortion and their hotline service. The data for this study includes one year of digital ethnographic work as a hotline volunteer at the abortion fund, along with in-depth interviews with the fund’s advocacy team. The fund organizers want to appeal to supporters, protect and empower communities, confront systemic oppression, and dispel medically incorrect, neoliberal (i.e. racist, sexist, and classist) anti-abortion myths. Due to societal stigma and silence, public abortion discourse is largely shaped by media (mis)representation. To combat misinformation and misogyny, reproductive justice (RJ) organizers disrupt mainstream abortion narratives with their own outreach. The organizers in this study use social media to interact with the public, supporters, donors, and anti-abortion activists alike. While these organizers publish anonymous data and stories from their hotline on social media, they also vigorously protect the privacy of their callers and hotline volunteers. The organizers recognize the importance of callers seeing their experiences represented in public discourse while also feeling protected from anti-abortion backlash. Therefore, I argue the abortion fund organizers carrying out this digital advocacy work are engaging in multifaceted emotional labor and putting their bodies on the line for a stigmatized issue. This study is informed by research that speaks to the promises and perils of new media for community building, movement organizing, and what Molina-Guzmán (2010) calls “symbolic rupture.” Social movement organizers work within the shifting media environment to transform cultural narratives, build solidarity, sustain their organizations, fundraise, and stand on the front line of stigmatized issues—even while enduring the consequences of personal exposure.